24 h combined esophageal multichannel intraluminal impedance and pH monitoring in children with chronic cough - Yi Gan; Xiaoqin Zhou; Zhaoxuan Huang; Shan Gao; Guirong Wang; Li Gu; Di Zhang; Lingzhi Yan; Shanshan Shang; Junhua Shu; Danna Tu (BMC, 2024)
Abstract Background Chronic cough in children is closely related to gastroesophageal reflux (GER). However, this association has not been adequately studied due to a lack of diagnostic tools. Combined esophageal multichannel intraluminal impedance and pH (MII-pH) monitoring is considered the most accurate method for evaluating the association between symptoms and reflux, but data on its use in children with chronic cough are still lacking. We aimed to assess the association between chronic cough and GER in children through MII-pH monitoring. Methods Children with chronic cough (> 4 weeks) who were suspected gastroesophageal reflux disease(GERD) were selected to undergo 24 h MII-pH monitoring at our hospital. Patients were divided into groups according to their age, body position, reflux index (RI) or total reflux events, and the differences between the groups were analyzed. Then the significance and value of 24 h pH and impedance monitoring in chronic cough and the relationship between chronic cough and reflux were discussed. Results Overall, 426 patients were included. The median age was 12 months (interquartile range: 6-39.5 months), 129 (30.3%) patients had RI > 7% detected by pH-metry, and 290 (68.1%) patients had positive diagnosis based on the impedance data. GER predominantly occurred in the upright position and mostly involved weakly acidic reflux and mixed gas-liquid reflux. There were 14.1% of children in non-acid GER group were SAP positive showing no difference in acid GER group 13.2% (P = 0.88), whereas patients with SAP > 95% in MII positive group (47[16.2%]) is higher than in MII negative group (P < 0.05). Conclusion Twenty four hour MII-pH monitoring is safe, well tolerated in children, but also has a higher detection rate of gastroesophageal reflux. It can find identify weakly acidic reflux, weakly alkaline reflux and reflux events with different physical properties, which can explain the relationship between GER and chronic cough more comprehensively. It provides new approach for exploring the etiology, diagnosis and treatment of children with chronic cough.